Orally administered prednisolone decreases plasma arginine vasopressin and serum copeptin concentrations in healthy dogs - Mathieu Victor Paulin; Dorsa Mehrabanpour; Suraj Unniappan; Elisabeth C. R. Snead (Journal of Veterinary Internal Medicine)
Abstract Background The pathophysiology of polyuria and polydipsia secondary to exogenous glucocorticoid excess is incompletely understood. Objective Investigate plasma AVP (pAVP) and serum CoP (sCoP) concentrations in healthy dogs before, during, and after abrupt discontinuation of a long‐term course of orally administered prednisolone. Animals Eight healthy neutered young adult research Beagles. Methods In our prospective longitudinal study, Beagles were treated with a placebo PO q24h for 15 days (baseline), followed by a 35‐day course of prednisolone (2.35‐2.75 mg/kg PO q24h) and then abrupt discontinuation of prednisolone. Serial pAVP and sCoP concentrations, urine specific gravity (USG) and calculated plasma osmolality (pOsmcalculated) were determined during placebo and prednisolone administration, and up to 4 weeks after prednisolone discontinuation. Paired plasma samples for pAVP measurement were obtained in EDTA tubes with (pAVPP800) and without (pAVPEDTA) a proprietary combination of protease, esterase, and dipeptidyl peptidase‐IV inhibitors (BD Biosciences P800). Results Mean pAVPP800 and sCoP concentrations were significantly lower at the end of the prednisolone course (25.8 ± 8.1 pg/mL and 166 pg/mL, range, 131‐223) vs baseline (34.1 ± 5.4 pg/mL and 243 pg/mL, range, 157‐336; P = .02, P = .02, respectively). Correlations between pAVPP800 and sCoP (r = .77, P = .001) and pAVPP800 and USG (r = .61, P = .02) were positive, despite no correlation between pAVPP800 and pOsmcalculated, sCoP and pOsmcalculated, and sCoP and USG. On paired samples, mean pAVPEDTA was significantly lower (5.0 ± 2.5 pg/mL) than mean pAVPP800 (34.1 ± 5.4 pg/mL; P < .0001). Conclusions and Clinical Importance Orally administered prednisolone led to markedly decreased plasma AVP and serum CoP concentrations despite increased calculated plasma osmolality and stable systolic blood pressure.